Polymers Based on Aniline as Active Materials for Li-Ion Accumulators. (4th December 2017) - Kazda, Tomáš; Zitka, Jan; Sedlarikova, Marie
Abstract : Polymers are mostly used as materials for separators and as binders of active materials in the electrodes. Thanks to that they are an inseparable part of Li-Ion accumulators nowadays. However, the use of polymers may also be different. There are polymers that exhibit relatively good conductivity and some also capacitive properties. Thanks to these properties, these polymers can be used as a conductive additives that replaces carbon and slightly increases capacity of electrodes. The capacity of certain polymers is comparable or higher than standard cathode materials, so they could be used also as active material of the electrodes. Materials based on copolymer of aniline were tested in this paper. All samples exhibit capacity between 50 and 80 mAh/g and good stability at high C rates, up to 5 C.